The Constitutional Organization in Argentina and the European 1848: the Case of Mariano Fragueiro - Wieczorek, Tomás (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
The intellectual history of the Argentine constitutional organization is marked by a series of ruptures and discontinuities regarding the political and its theoretical references. If in the second half of the nineteenth century the “the lack of originality” of the 1853 constitution thesis prevailed, at the dawn of the 20th century, the interpretive sign would be radically disrupted, in order to celebrate the originality of the Alberdian work. Towards the middle of the last century, it would be the revisionist −or militant− historiographical school the one that would warn that the main theoretical-political references of Argentine constitutional thought, are incardinated in the horizon of the European 1848 revolution. The present paper aims to restore the modes of appropriation and distancing in this regard of Mariano Fragueiro, self-proclaimed socialist and first constitutional finance minister of the Argentine Confederation.
Keywords: Argentina; Constitution; Socialism; Fragueiro.